Pelatihan Pembuatan Jamu Kunyit Asam di SMA Wahidiyah Kota Kediri - Sony Andika Saputra; Jihan Roselina Putriaji; Fena Rofi’atun; Arzety Elmadiasmara Putri; Heryed Aprilia Dungku; Apriyanto F.G.S JIE; Arya Ulilalbab (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Jamu is a traditional Indonesian herbal drink believed to have health benefits and has been preserved to this day. One type, turmeric and tamarind jamu, is known to effectively alleviate menstrual cramps naturally. The workshop on making turmeric and tamarind jamu at Wahidiyah High School in Kediri City on May 17, 2025, aimed to enhance students' knowledge and skills in preparing jamu hygienically. The activity was attended by 15 students from grades 10 and 11, using methods such as lectures, discussions, leaflets, and hands-on practice. Evaluation results showed an average increase in knowledge scores from 76.4% to 97.9%, particularly in terms of cleanliness and storage. This workshop not only educated students about the benefits of jamu but also fostered cultural awareness and entrepreneurial potential. The turmeric and tamarind herbal medicine education program at SMA Wahidiyah successfully improved students' knowledge and skills in preparing herbal medicine hygienically, with significant improvements in hygiene and storage aspects. In addition, this activity is expected to be the first step in introducing herbal medicine as a natural health product that has the potential to be developed further.